The Musical Form of the Gondang Borogong Ensemble among the Malay Community in Tangun Village, Rokan Hulu Regency, Riau - Regina Lastiarma Br Sinaga; Rithaony Hutajulu; Vanesia Amelia Sebayang (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2025)
This research focuses on the musical form of the Gondang Borogong ensemble within the Malay community of Tangun Village, Bangun Purba District, Rokan Hulu Regency, Riau Province. The purpose of this study is to describe the musical form of Gondang Borogong. The method used in this study is a qualitative-ethnographic method to examine the musical form of the Gondang Borogong ensemble within the Malay community of Tangun Village. The ethnographic approach allows for a holistic understanding of the musical structure, social function, and cultural significance of this music. The Gondang Borogong ensemble consists of several main instruments: gongs, calempongs, and drums. In its presentation, this art is generally performed at joyful events such as thanksgiving, weddings, and welcoming important guests, which are usually accompanied by martial arts (silek) performances. The repertoire commonly performed by this ensemble includes Sasatu, Duo-duo, Tigo-tigo, Kukubiek, Tulak Serantau, Orang Kayo Belimau, and Taktuntun.